Entrepreneurship Learning Analysis on The Interest Entrepreneur Trough Subjective Norm and Attitudes in Students Of Economic Faculty Economy UNPAZ - Silva, Jose da (International Journal of Review Management Business and Entrepreneurship (RMBE), 2021)
This study aims to determine the effect of the interested entrepreneur to entrepreneur learning through subjective norms and attitudes on Unpaz Students of the Faculty of Economics. The method used in this research is a quantitative method by using Structural Equation Modeling (SEM) AMOS. The sample used in this study were students UNPAZ Faculty of Economics majoring in Accounting, Management, and Banking totaling 187 students. This research data collection methods by using a questionnaire with Likert scale. The results of this study are entrepreneurial learning, subjective norms, attitude to entrepreneurs have a significant and positive influence on entrepreneurs’ intention. Meanwhile, entrepreneurial learning also has a significant and positive effect on the subjective norm. Four variables showed Da Paz implication that the University should provide an opportunity to the students a lot of activity in the field, sharing with colleagues who merged his business. Students are taught to try to learn the business from the communities around and from an entrepreneurial family background, always creative and read a great opportunity to succeed and never give up until achieving success